Neutralization Sensitivity of HIV-1 CRF07_BC From an Untreated Patient With a Focus on Evolution Over Time - Wang, Lijie; Liang, Shujia; Huang, Jianhua; Ding, Yibo; He, Lin; Hao, Yanling; Ren, Li; Zhu, Meiling; Feng, Yi; Rashid, Abdur; Liu, Yue; Jiang, Shibo; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Diversity of HIV-1 envelope (Env) glycoproteins affects the potency and breadth of broadly neutralizing antibodies (bNAbs), a promising alternative to antiretroviral drugs for the prevention and treatment of HIV-1 infection. To facilitate immunogen design and development of therapeutic neutralizing antibodies, we characterized viral evolution and monitored the changes in neutralizing activity/sensitivity of a long-term non-progressor patient with HIV-1 CRF07_BC infection. Fifty-nine full-length Env gene fragments were derived from four plasma samples sequentially harvested from the patient between 2016 and 2020. Sequencing of patient-derived Env genes revealed that potential N-linked glycosylation sites (PNGS) in V1 and V5 significantly increased over time. Further, 24 functional Env-pseudotyped viruses were generated based on Env gene sequences. While all 24 Env-pseudotyped viruses remained sensitive to concurrent and subsequent autologous plasma, as well as bNAbs, including 10E8, VRC01, and 12A21, Env-pseudotyped viruses corresponding to later sampling time were increasingly more resistant to autologous plasma and bNAbs. All 24 Env-pseudotyped viruses were resistant to bNAbs 2G12, PGT121, and PGT135. The neutralization breadth of plasma from all four sequential samples was 100% against the global HIV-1 reference panel. Immune escape mutants resulted in increased resistance to bNAbs targeting of different epitopes. Our study identified known mutations F277W in gp41 and previously uncharacterized mutation S465T in V5 which may be associated with increased viral resistance to bNAbs.